THE IMPLEMENTATION OF TASK-BASED LANGUAGE TEACHING TO TEACH SPEAKING DESCRIPTIVE TO THE FIRST GRADERS OF JUNIOR HIGH SCHOOL - YUNIARISDA H, EVI (RETAIN : Journal of Research in English Language Teaching, 2014)
THE IMPLEMENTATION OF TASK-BASED LANGUAGE TEACHING TO TEACH SPEAKING DESCRIPTIVE TO THE FIRST GRADERS OF JUNIOR HIGH SCHOOL Evi Yuniarisda Hutagalung English Education Department, Language and Arts Faculty, Surabaya State University. Email: veeyah@rocketmail.com Dr. Oikurema Purwati, M.Appl English Education Department, Language and Arts Faculty, Surabaya State University. Abstrak Berbicara adalah keterampilan paling penting yang harus dikuasai oleh siswa EFL. Namun, siswa menganggap keterampilan berbicara sebagai keterampilan yang paling sulit untuk dicapai. Untuk mengatasi hal ini, guru sebaiknya menggunakan sebuah pendekatan yang dapat memotivasi siswa untuk berbicara. Salah satu pendekatan yang dapat digunakan adalah task-based language teaching yang telah terbukti dapat memajukan progress akademik siswa dan keterampilan berinteraksi. Sayangnya, studi tentang task-based language teaching di kelas-kelas SMP di Indonesia sangatlah jarang. Oleh karena itu, penting untuk melakukan penelitian tentang ini. Task-based language teaching merupakan pendekatan dalam mengajar bahasa inggris yang menitikberatkan pada penggunaan tugas bersifat mendidik yang merupakan tugas kelas yang melibatkan siswa dalam memahami, memanipulasi, memproduksi atau berinteraksi dalam target bahasa dimana mereka lebih fokus pada pemahaman daripada bentuk. Task-based language teaching dipercaya dapat memajukan progress akademik siswa dan keterampilan berinteraksi. Singkatnya, task-based language teaching memungkinkan siswa untuk memproduksi target bahasa melalui penyelesaian tugas yang komunikatif. Penelitian ini bermaksud untuk mendeskripsikan implementasi dari task-based language teaching untuk menagajar berbicara deskripsi pada siswa kelas satu SMP Negeri 26 Surabaya dan untuk mendeskripsikan kemampuan berbicara siswa setelah implementasi tersebut. Desain penelitian ini adalah penelitian kualitatif. Untuk melaksanakan penelitian ini, field notes digunakan sebagai instrumen yang memiliki komponen-komponen, yaitu bagian deskripsi dan bagian refleksi. Data yang dikumpulkan adalah data deskriptif yang lebih fokus pada kata-kata daripada angka atau statistic. Sumber data adalah field notes yang mendeskripsikan detail dari implementasi task-based language teaching dan juga transkrip siswa yang mendeskripsikan kemampuan berbicara mereka. Subyek penelitian ini adalah guru dan siswa SMP Negeri 26 Surabaya, terutama siswa kelas VII F. Hasil dari penelitian ini adalah bahwa implementasi task-based language teaching untuk mengajar berbicara deskripsi dilaksanakan tepat dan sukses sesuai dengan framework yang diusulkan oleh Ellis. Task-based language teaching sangatlah menarik dan memotivasi siswa karena siswa ditantang untuk menyelesaikan tugas yang bersifat komunikatif. Terdapat interaksi di antara siswa. Kemampuan berbicara siswa setelah implementasi tas-based language teaching pada pertemuan pertama dan kedua juga memuaskan. Kata Kunci: task, task-based language teaching, berbicara, descriptif, SMP. Abstract Speaking is concerned as the most important skill that must be mastered by EFL students. However, students regard speaking as the most difficult skill to attain. To overcome this, teachers should use an approach which motivates students to speak. One of the approaches is task-based language teaching which has been proven to promote learners’ academic progress and interaction skills. Unfortunately study about task-based language teaching in junior high classroom in Indonesia is rare. Therefore, it is necessary to conduct a research about this. Task-based language teaching is an approach in teaching English which emphasize on the use of pedagogical task which is a piece of classroom work that involves learners in comprehending, manipulating, producing or interacting in the target language while their attention is primarily focused on meaning rather than form. Task-based language teaching is believed to promote students’ academic progress and interacting skills. In short, task-based language teaching enables the students to produce the target language through the completion of communicative task. This research aims to describe the implementation of task-based language teaching to teach speaking descriptive to the first graders of 26 State Junior High School and to describe the students’ speaking ability after the implementation. The design of this research is a qualitative research. To conduct the research, field notes were used as the instrument which components are descriptive part and reflective part. The data collected was a descriptive data which focus on words rather than numbers or statistics. Source of the data were field notes which described the detail of the implementation of task-based language teaching and students’ transcription which describes the students’ speaking ability. The research subjects were the teacher and the students of 26 Junior High School Surabaya, especially the students of VII F Class. The result of this research is that the implementation of task-based language teaching to teach speaking descriptive was conducted properly and successfully according to the framework suggested by Ellis. It was very engaging and motivating because the students were challenged to complete a communicative task. There was a good interaction among the students. Students’ speaking ability after the implementation of task-based language teaching on the first and on the second meeting was satisfying. Keyword: task, task-based language teaching, speaking, descriptive, junior high school. INTRODUCTION Increasing speaking ability is concerned as the most important objective of teaching English. Unfortunately, in the field, numerous students cannot even express their thoughts. Malihah (2010) states that among the four language skills, learners regard speaking as the most difficult skill to attain because it needs great courage as well as preparation to produce the language. Many students only learn English at the surface. That is, they only learn about sentence structure, such as grammar which includes; tenses, modals, passive voice, etc. Of course, this language component is something important. However, if the process of learning English is only focused on the sentence structure, a question of when the students will speak to express their ideas and feelings would appear. It is surely known that this has been a problem in learning English. Students learn English, but they never use the language to speak. This is, of course, not the prime objective of learning English. According to the Standard Competence 2013 for the first graders of junior high school, students are expected to be able to produce spoken descriptive text. “4.12. Menyusun teks deskriptif lisan dan tulis, sangat pendek dan sederhana tentang orang, binatang, dan benda, dengan memperhatikan fungsi sosial, struktur teks, dan unsur kebahasaan, secara benar dan sesuai dengan konteks” (Gunawan, Khatimah et al. 2013). In mastering the goal, the students have to be able to use the language feature such as when to use the article of ‘a’ and ‘an’, to use subjects and possessive pronouns, to distinguish the plural and singular noun, etc. In the other words, students are expected to be able to produce a very simple spoken descriptive text about something or someone. Descriptive text is a kind of text which consists of specific description about a person, an animal, or a thing. Students are expected to be able to describe the characteristics and behaviors of a person, an animal, or a thing. Hence, teachers are indeed expected to activate students’ motivation and skill to do so. To meet the goal of this learning, teachers can try to use some approaches which enable students to speak. One of the approaches is Task-Based Language Teaching. Task-Based Language Teaching (TBLT) has been developed during the last twenty years. Its characteristic as a learner-centered approach makes it becomes a highly recommended approach to be used by EFL teachers. Task-Based Language Teaching itself is an approach which emphasizes on the process of learning to communicate through interaction in the target language (Nunan 2004). Through this approach, the students are trained to concentrate their minds not only to learn the structure of a language, but also to produce the language. This is in line with the principles that task-based language teaching is the stipulation of opportunities for students to focus not only on language but also on the learning process itself (Nunan 2004). Nunan (2004) states that task-based language teaching represents a realization of communicative language teaching philosophy. Malihah (2010) states that the communicative language teaching focuses more on language learning as interaction, and meaningful communication becomes the main point rather than the complexity of grammar rules. Therefore, task-based language teaching will stimulate the students to talk more during the learning process like talk about themselves, to have a joke, deliver some ideas and thoughts, without being hesitated or afraid from making some mistakes or errors of the grammar. They just have fun whilst they are doing the task. Dailey (2010) also believes that TBL has its valuable points and is a new, exciting, and interactive approach to improve communicative competence. According to Freeman (2000) TBLT is an approach which intends to provide students with natural situation for language utilization. This approach allows the student to have the opportunity to actualize themselves through conversational English. As stated by Freeman (2000) when student are instructed to complete a task, they surely have a lot of opportunities to interact one another. This kind of interaction enables the students to acquire some language uses and expressions that are beyond their conjecture. This is due to the fact that they have to try to understand one another to solve the problems in a task they are doing. According to the notions of TBLT stated above, it is clearly seen that TBLT can be used as an approach to reach the target language in learning English; producing target language through interaction. Through the implementation of TBLT, it is hoped that learners become aware of the importance of using language to interact and to communicate. By implementing this approach, many teachers are also expected to change their traditional ways of teaching to become more engaging, challenging, and giving more experiences through the tasks which stimulate the students to learn by doing. The advantages of task-based language teaching stated above are in line with the research done by He and Lin. He and Lin (2004) found that implementing the TBLT can stimulate the learners to work together in groups. The research found that students learned something real when carrying out real-world tasks in pairs/groups, not leaning something on books. Every student in the class had his own characteristics and parts which enable them to learn from each other when they are interacting together (He and Lin 2004). A research conducted by Hadi (2012) has proven some benefits gained from implementing the task-based language teaching into a classroom. This research was conducted using perception questionnaires as the instrument. The results of the research show that TBLT promotes learners’ academic progress (36.4% of the students’ vote), TBLT improves learners’ interaction skills” (80.7% of the students’ vote), “TBLT encourages learners’ intrinsic motivation” (56.8% of the students’ vote), “TBLT creates a collaborative learning environment” (75% of the students’ vote), and finally “TBLT is appropriate for small group work” (71.6% of the students’ vote). In addition, a research conducted by Xiongyong and Samuel (2011) found that task-based language teaching exposes that most EFL teachers had positive attitudes toward TBLT execution due to a higher level of understanding of task and TBLT concepts. Hence, some of the participating teachers decided to apply TBLT which is believed to encourage students’ intrinsic motivation (81.6%), enhance students’ interactive strategies (75.7%), and generate a collaborative learning environment (73.8%). By contrast, the smaller percentages argued that TBLT promotes students’ academic progress (63.1%) and adapts to small group work (68.9%). The other category (4.9%) involves the diversity of promotion of students’ learning interest and initiatives. Finally, Candlin and Murphy (1987) state that the central of the teachers concern is language learning, and tasks offer this in the form of a problem-solving compromise between knowledge that the students have already known and new knowledge. Thus, the students will use the language to communicate. They speak. However, studies about TBLT are rare. Moreover there is no study about the implementation of TBLT in junior high classrooms in Indonesia. In fact, this study is needed to see the stages of implementing TBLT in junior high classrooms. In addition, this study is beneficial to describe the students’ speaking ability after implementing TBLT. Thus, many teachers will understand the correct phases or stages in implementing TBLT and will see the students’ speaking ability after the implementation. Method Design that was used in this research was a qualitative research. The researcher used a qualitative research design because it is less subjective. By using this research design, the researcher could observe the implementation of task-based language teaching the way it was. The result of the research was also very objective. The subjects of this research are the teacher and the first graders of 26 Junior High School Surabaya, especially the students of VII F classroom. The researcher chose 26 State Junior High School because it is one of some junior high schools in Surabaya that has been chosen to firstly implement the curriculum of 2013. The researcher felt a necessity to observe the implementation of task-based language teaching and the students’ speaking ability after the implementation according to the recent curriculum rather than the older one. The researcher chose VII F students because according to the teacher the English proficiency of the students varied. The researcher used field notes as instrument to conduct the research. Field notes contain everything that the researcher will see and heard. The researcher did a non-participant observation as a technique to collect the data needed to answer the research questions. Non-participant observation is less subjective which latter involves observing actions and interactions, perhaps sitting in a corner of the room, silent, but attentive (Koshy 2005). Ary et. al (2010) named this kind of observation as complete observer who simply observes and records events as they occur. No attempt is made to alter the situation in any way. This was also done by the researcher. The researcher sat in the corner of the classroom and observed the teacher who implemented task-based language teaching. Result and Discussion Result Firstly, the researcher will describe the result of the research which answers the first research question; how is the implementation of task-based language teaching to teach speaking descriptive to the first graders of junior high school. On the first meeting, in the pre-task, the teacher asked the students to mention the things in the classroom. This was done to stimulate the students’ motivation to learn. Next, the teacher showed the students a picture of a room on slide-show. The teacher asked them to describe the room they saw. After giving the students a chance to describe and mention the things in the picture, the teacher explained a little bit about the simple present tense, the use of “there is” and “there are”, articles ‘a’ and ‘an’, subjects and possessive pronouns, and singular and plural nouns. Subsequently, the teacher came to the next stage of implementing the task-based language teaching in the classroom which was the during-task. In this stage, the teacher asked the students divide themselves into seven groups. Two groups consisted of four students and five groups consisted of five students. The teacher instructed each group to describe parts of a house. The teacher gave the students fifteen minutes to discuss about what they were going to say to describe the picture. The teacher observed the class actively and always advised the students to keep speaking in English. The teacher warned some of them who spoke in Indonesia or Javanese. In the last stage, post-task, the teacher evaluated the students’ work in front of the class. The teacher called the group one by one to come forward and present their works orally. Every member of the group took turn to describe the picture he/ she got at least two sentences. After that, the teacher asked him/ her to write what he/ she had said on the whiteboard. This was done so the other students could check their friends’ sentences and then correct what might have been incorrect. After the first three groups presented, the teacher started to evaluate the students’ work. He checked the text written on the whiteboard and also invited the students to check it too. Some students were so eager to evaluate their friends’ works. Some of them stated the incorrect expressions and sentence structures made by their friends. The teacher let them to correct the text. Most students had awareness of the errors in the text. The teacher continued to call the other groups and revised their utterances. After giving the evaluation to all of the groups, the teacher stimulated the students to ask the things they did not understand yet. No student questioned. All of the students seemed like they had already understood. The post-task stage had been done successfully. The teacher closed the process of teaching learning. The teacher closed the lesson. On the second meeting, the teacher reviewed the lesson on the previous meeting. All of the students showed good response which meant that they still remembered about what they had learned before. After reviewing the lesson on the previous meeting, the teacher remarked that they would conduct a puzzle game. Next, the teacher mentioned some conditions while playing the game that the students should play fairly, use English when interacting, and finish the game in five minutes. The students agreed with the conditions. The teacher divided the class into seven groups. There were one group consisted of three students, one group consisted of six students, two groups consisted of four students, and three groups consisted of five students. The teacher instructed the each group to make a circle. After that, the teacher distributed the puzzle to each group. The puzzles were all different. In the during-task, the teacher started the game and let the students to finish their puzzles. The teacher also observed the students. In the last stage, post-task, the teacher called each group to come forward to present their works. Each member of the group had to describe the picture in the puzzle they had arranged. When the student was describing the picture, the teacher wrote any mistakes and errors made by the student. The teacher evaluated the students after each group performance. Next, the researcher will describe the result of the research which answers the second research question; the students’ speaking ability after the implementation of ask-based language teaching. The first meeting: Group One Describing a classroom This is my classroom. My classroom is orderly. (AKT: 04). There are three pens colors purple, green, and pink. There are three pictures. (FAN: 15). There is one ruler. There are two erasers of soft. (FIT: 18). There are six chairs of make from wood for students. There is one cupboard at the corner of class. (IKF: 20). There is a vase pretty. There are seven tables. There is one book above a table. (SIN: 35). From the transcript we can see that group one made only few mistakes. AKT gets the highest score because she made almost no mistakes. Her grammar and vocabulary were very good. She could even speak very fluently. It seemed that she could comprehend every word she said although her pronunciation is not perfect. AKT’s score was 4 for pronunciation, and 5 for grammar, vocabulary, fluency, and comprehension. The second speaker from group one was FAN. FAN made a little mistake by saying “there are three pens colors purple, green, and pink” which is grammatically wrong. She should have said “there are three pens. They are purple, green, and pink” or “there are three pens. The pens are purple, green, and pink”. Her pronunciation was good enough so she got 4 for her pronunciation. Because she made a little bit mistakes grammatically, she also got 4 for grammar. Her vocabulary and comprehension were also good enough that she got 4 for each component. However, she got 3 for fluency, because she spoke rather strongly affected by language problem. She did some repetition when she spoke. The third speaker was FIT. Her pronunciation was good enough that she got 4 for it. However her grammar, fluency, and, comprehension were not good that she got 3 for each component. She said “There are two erasers of soft” which was grammatically wrong. She should have said “There are two soft erasers”. Similar to FAN, FIT also spoke rather strongly affected by language problem. She did some repetition when she spoke. The fourth speaker was IKF. IKF got the second best score after AKT. Her pronunciation, grammar, fluency, and comprehension were good that she got 4 for each component. And her highest score was at vocabulary that she got 5 for it. She used many vocabularies. Although she made a little bit mistakes grammatically by saying “There are six chairs of make from wood for students”, but it was still understandable. The last speaker of group one was SIN. She got the third best score after AKT and IKF. All of the language components were 4. Although she made a little bit mistakes by saying “there is a vase pretty”, but the sentence was understandable. The sentence she stated should have been “there is a pretty vase”. She spoke fluently enough. Group Two Describing a living room This is my living room. My living room is clean. Emmm, there are three pictures (ADD: 01). There is sofa. It is brown. There is a table. It is black (DEV: 10). There is a. There is. There is a bookcase. It is brown. There is a telephone. It is blue (FRH: 16). There is a television. Television is…is beside telephone. Television is blue. There are floors. It is white. There is a carpet (FRN: 17). There are ‘certains’ (curtains). They are red. There is a wall. It is yellow. Emm, there are windows. There is a plant. It is green (RAT: 33). ADD’s pronunciation and fluency was good that she got score 4 for each component. Her grammar was perfect. She made no mistake. She also used enough vocabulary. She seemed comprehended what she was trying to say. Therefore she got score 5 for grammar, vocabulary, and comprehension. DEV forgot to add an article ‘a’ when she said “there is sofa”. It should have been “there is a sofa”. However, it did not obscure the meaning. Her fluency, vocabulary, and comprehension were not categorized as good, but enough. Therefore, she got score 4 for pronunciation and grammar and score 3 for fluency, vocabulary, and comprehension. FRH got score 4 for pronunciation, grammar, and vocabulary, and comprehension. Her pronunciation was good. She also made almost no mistake grammatically. She stated enough vocabulary. It also seemed like she understood what she was trying to say. However, her fluency was scored 3 because she often made pauses when she spoke. FRN got score 4 for pronunciation, vocabulary, and comprehension. However, he got score 3 for grammar and fluency. He made some mistakes by saying: “There are floors. It is white”. Floors are plural nouns that he should have been said: “The floors are white”. He did not speak fluent because he sometimes stopped when he spoke and seemed like thinking. RAT got score 3 for pronunciation because she pronounce ‘curtains’ as ‘certains’. Her grammar was perfect that she got 5 for it. She made no grammar error. Her vocabulary, fluency, and comprehension also got 5 for each. The second meeting: No. Name Transcription 19. IGN There is. There are. There is one whiteboard. This is my class. There is a whiteboard. 29. NYI My class, there are three pictures. 6. AND There is one whiteboard. There are eleven computers. 24. MEG Pause for while. There are three pictures. 22. KHO There are is seven table. IGN as the first speaker got score 4 for pronunciation because his pronunciation was good. He grammatically made no mistakes that he got score 5 for it. He stated enough vocabulary that he got 4 for vocabulary score. However, his fluency was scored 3 because he did repetition when he spoke. His comprehension was good that he got 4 for it. NYI got score 4 for pronunciation and grammar. Her pronunciation was good. Her grammar was also good. She said “My class. There are three pictures”. This would have been more correct if she said “There are three pictures in my class”. She used only few words which indicated vocabulary limit. Therefore, she got score 3 for vocabulary. It needed sometimes for her to say a word. Her fluency was poor that she got score 2 for fluency. Her comprehension was scored 3. AND’s pronunciation was good. He only pronounced ‘computers’ like in Indonesia ‘komputers’. His grammar was perfect. He made no mistake grammatically. He stated enough vocabulary that it was good and was scored 4. However his fluency was poor that he got 2 for it. It needed sometimes for him to say a word. His comprehension was good. MEG’s pronunciation was good. Her grammar was perfect because she made no mistakes. She used only few words that she got 3 for it. She seemed confused to choose a vocabulary. Her fluency was poor because she took time to speak. She paused for a while to just say a sentence. Her comprehension was scored 3. KHO’s pronunciation was good. Her grammar was scored 3 because she was still confused whether to use ‘are’ or ‘is’. Her vocabulary was also scored 3 because she only said a short sentence. It seemed difficult for her to choose a vocabulary. Her fluency was poor because she took time to just say each word. Her comprehension was scored 3. No. Name Transcription 32 RAR This is store. This is a ‘snack=snake’ This is people. And this wall is grey. 30 QUD The calendar above on, in, on the on the aquarium. The student stand up on stand up on the floor. 31 QUI This is a store. There is a freezing machine. There is a glass cabinet. And then a customer. And then some food sell there. RAR’s speaking aspects were all categorized as fair. He pronounced the word ‘snack’ as ‘snake’. He also made grammar error by saying “this is people”. The sentence would have been grammatically correct if it is said “there are some people”. His vocabulary and comprehension were also enough. QUD’s pronunciation was good that she got score 4 for it. However, her grammar was poor because she made some grammar mistakes. She was confused to use the correct preposition and it occurred several times. She states enough vocabulary. Her fluency was poor because she made a lot of repetition. Her comprehension was enough. QUI’s pronunciation and grammar were scored 4. She got score 5 for vocabulary, fluency and comprehension. QUI’s pronunciation was good and clear. Her grammar was also good. She only made mistake by saying “some food sell there”. The sentence should have been “some foods are sold there”. However this was fine because QUI’s utterance was still understandable. Her utterance did not obscure the meaning at all. She could use varying vocabulary, such as freezing machine and glass cabinet. Therefore, she got perfect score for vocabulary. She spoke fluently and comprehended what she was saying well. Discussion In this part, the researcher will discuss the result of the research in the relation of the theory. On the first meeting, in the pre-task stage, the teacher organized the students to make some groups. There were five groups consisted of five students and the other two consisted of four students. The teacher instructed each group to describe a picture of a classroom and parts of a house. There were seven pictures of parts of a house and a classroom. The teacher explained a little bit about the simple present tense, the use of “there is” and “there are”, articles ‘a’ and ‘an’, subjects and possessive pronouns, and singular and plural nouns. The students were so quiet and enthusiastic to listen to the teacher’s explanation. In the second stage or during stage, the teacher gave the students fifteen minutes to think about what they were going to say to describe the picture. Before letting the students did the group discussion, the teacher had stated that the teacher would not help them at all. The students should work themselves. This is in line to what Willis suggests. According to Willis (1996), in this stage, teachers shouldn’t help the students. Teachers should let them work themselves to construct the sentences and the language expression they would use. During the post-task, the students worked together in groups well. This is in line to the finding that task-based language teaching can stimulate the learners to work in groups (He and Lin 2004). In the last stage or the post-task stage, the teacher evaluated the students’ work in front of the class. The teacher called the group one by one to come forward and present their works orally. Every member of the group took turn to describe the picture by mentioning the things in the picture. After that, the teacher asked him/ her to write what he/ she had said on the whiteboard. This is done so the other students could also check their friends’ works. Evaluation or feedback is important to gain students’ knowledge about what is correct and incorrect. Task-based language teaching helped the students in the form of a problem-solving compromise between knowledge that the students have already known and new knowledge (Candlin and Murphy 1987). On the second meeting, in the pre-task stage, the teacher reviewed the lesson on the previous meeting. On this meeting, the teacher explained a little bit more about the simple present tense. After that, the teacher remarked that they would conduct a puzzle game. Next, the teacher mentioned some conditions while playing the game that the students should play fairly, use English when interacting, and finish the game in five minutes. Next, the teacher divided the class into seven groups. The teacher instructed each group to make a circle. After that, the teacher distributed the puzzle to each group. In during stage, the puzzle game started. The teacher moved around the class and observed the students. Like always, the teacher, asked the students to speak in English while solving the game. Through the completion of this puzzle, the students were challenged to finish the task fast. They were trained to work in team to solve the problem. While solving the problem, they used the target language. Although sometimes some of them still use Bahasa Indonesia, but they still tried to speak in English while they are interacting with their friends. This is in line to the findings done by Hadi. Hadi (2012) has proven that task-based language teaching improves students’ interaction skills. In the post-task stage, the teacher called each group to come forward to present their works. Each member of the group had to describe the picture in the puzzle they had arranged. When the student was describing the picture, the teacher wrote any mistakes and errors made by the student. After that, the teacher conducted an evaluation towards the students’ works. In conclusion, what the teacher did on the first meeting and the second meeting were all in line to the framework of task-based language teaching suggested by Ellis. According to Ellis (2006) there are three stages in implementing task-based language teaching in a classroom, which they are the pre-task stage, the during stage, and the post-task stage. Therefore, task-based language teaching was implemented properly and successfully. The teacher also understood the notion of the task given to the students. The task was designed not only to be completed, but also to reach the communicative purpose in order to achieve an outcome Willis (1996). It can be seen from the first and the second meetings that all of the students tried to not only complete the task given by the teacher, but also produce the language. On the first meeting, five students were absent. There were thirty three students in the classroom participated in this research. Therefore, the average score of each language component of students’ speaking ability was divided to thirty three. Whereas, on the second meeting, six students were absent. There were thirty two students in the classroom participated in this research. Therefore, the average score of each language component of students’ speaking ability was divided to two. The researcher concluded the final result of the students’ speaking ability by drawing the average score from the first and the second meetings. These are the description of the students’ speaking ability on the first and the second meeting using the speaking proficiency suggested by Harris (1969): The students’ average score of pronunciation was good. This scale of pronunciation is categorized as intelligible, though one is conscious a definite accent. Most of the students pronounce the words correctly and clearly, though some of them still have worse pronunciation which was influenced by the pronunciation of Indonesia. The students’ average score of grammar was good. This scale of grammar indicates that most of the students occasionally made grammatical and/ or word order errors which did not obscure meaning. The students’ average score of vocabulary was good. According to Harris (1969) this scale of vocabulary indicates that the students sometimes use inappropriate terms and/ or must rephrase ideas because of lexical of inadequacies. This is true that some of the students in VII F occasionally used inappropriate terms. The students’ average score of fluency was good. This scale of fluency indicates that the students speed or speech seems to be slightly affected by language problems. The students’ average score of comprehension was good. This scale of comprehension indicated that the students understood nearly everything at normal speed, although occasionally repetition might be necessary. In conclusion, the students’ speaking ability after the implementation of task-based language teaching was satisfying. This finding showed that implementing task-based language teaching to teach speaking descriptive to the first graders of 26 State Junior High School effects on positive results on students’ speaking ability. This finding equals to the finding done by Xiongyong and Samuel (2011) which found that task-based language teaching promotes learners academic progress. CONCLUSION AND SUGGESTION Conclusion According to this research, it is concluded that the implementation of task-based language teaching to teach speaking descriptive to the first graders of junior high score was conducted properly and successfully according to the framework suggested by Ellis. The implementation was effective to engage and motivate the students to speak descriptive actively through the completion of a communicative task. The students’ speaking ability after the implementation on the first and the second meeting was satisfying. Most of the students got satisfying scores in speaking descriptive. Suggestion After explaining the results of this research and drawing conclusions, it is suggested to choose the suitable task for the students. The task should be engaging and motivating. The task is aimed not only to be completed but also should give communicative goals. Look for the solutions to the issue that task-based language teaching has possibilities to make the class noisy and hard to control since the students become very active during the learning process. REFERENCES Ary, D., L. C. Jacobs, et al. (2010). Introduction to Research in Education. Belmont: Cengage Learning. Candlin, C. and D. F. Murphy (1987). Language Learning Task. Englewood Cliffs: Prentice-Hall. Corbin, J. and A. Strauss (2008). Basics of Qualitative Research: Techniques and Procedures for Developing Grounded Theory. California: Sage. Ellis, R. (2003). Task-Based Language Learning and Teaching. Oxford: Oxford University Press. Ellis, R. (2006). The Methodology of Task-Based Teaching. Asian EFL Journal 8(3). Finnocchiaro, M. (1975). Visual Aids in Teaching English as a Second Language. Washington D.C: English Teaching Forum. Freeman, D. L. (2000). Techniques and Principles in Language Teaching. Oxford: Oxford University Press. Gunawan, A., Y. R. Khatimah, et al. (2013). Bahasa Inggris: When English Rings the Bell: buku guru/Kementrian Pendidikan dan Kebudayaan. Jakarta: Kementerian Pendidikan dan Kebudayaan. Hadi, A. (2012). Perceptions of Task-based Language Teaching: A Study of Iranian EFL Learners. English Language Teaching 6(1): p103. Harris, D. P. (1969). Testing English as Second Language. New Delhi: McGraw-Hill. He, T. and J. Lin (2004). Implementing Task-Based Approaches Into Elementary School EFL Classes in Taiwan. The proceedings of the 13th International Symposium on English Teaching. Johnson, K. and K. Morrow (1981). Communication in the Classroom: Applications and Methods for a Communicative Approach. ERIC. Kayi, H. (2006). Teaching Speaking: Activities to Promote Speaking in a Second Language. The Internet TESL Journal 12(11). Koshy, V. (2005). Action Research for Improving Practice. London: Paul Chaoman Publishing. Malihah, N. (2010). The Effectiveness of Speaking Instruction through Task-Based Language Teaching. REGISTER 3(1): 85-101. Murcia, C. C. M. (2001). Teaching English as a Second or Foreign Language. Boston: Heinle&Heile. Nunan, D. (1989). Designing Tasks for the Communicative Classroom. Cambridge: Cambridge University Press. Nunan, D. (2003). Practical English Language Teaching. Singapore: McGraw-Hill. Nunan, D. (2004). Task-Based Language Teaching. Cambridge: Cambridge University Press. Prabhu, N. S. (1987). Second Language Pedagogy. Oxford: Oxford University Press. Willis, J. (1996). A Framework for Task-Based Learning. New Jersey: Pearson PTR. Xiongyong, C. and M. Samuel (2011). Perceptions and Implementation of Task-based Language Teaching among Secondary School EFL Teachers in China. International Journal of Business and Social Science 2(24).